Piezoelectric composite material, method for preparing the same and use thereof

CN117177650BActive Publication Date: 2026-10-23NINGBO UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310686499.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2026-10-23
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

但目前关于利用金属掺杂提升基于双钙钛矿@PVDF薄膜PENG的性能,还没有相关研究

Benefits of technology

[0025]1、本发明所制得的压电复合材料为基于Zr/Te共掺的Cs2Ag0.3Na0.7InCl6双钙钛矿@PVDF复合膜,测试结果表明相对于Cs2Ag0.3Na0.7InCl6双钙钛矿填料,在PVDF基体中掺入Zr/Te共掺的Cs2Ag0.3Na0.7InCl6双钙钛矿填料可以显著提高β相含量,通过合理添加Zr和Te的掺杂量可以显著提高Cs2Ag0.3Na0.7InCl6晶体的极性,从而形成强大的内嵌电场,以提升复合膜的介电性能和自发极化效应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117177650B_ABST
    Figure CN117177650B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of piezoelectric materials, and relates to a piezoelectric composite material and a preparation method and application thereof. 0.3 Na 0.7 InCl6 double perovskite@PVDF composite film, relative to Cs2Ag 0.3 Na 0.7 InCl6 double perovskite filler, Zr / Te co-doped Cs2Ag 0.3 Na 0.7 InCl6 double perovskite filler can significantly improve the content of the beta phase, and by reasonably adding the doping amount of Zr and Te, the content of the beta phase can be significantly improved. 0.3 Na 0.7 The polarity of the InCl6 crystal is improved, so that a strong internal embedded electric field is formed, thereby improving the dielectric performance and spontaneous polarization effect of the composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of piezoelectric materials technology, and relates to a piezoelectric composite material, its preparation method and application. Background Technology

[0002] The energy crisis has made the search for new, sustainable energy sources urgent. Mechanical energy, due to its abundant sources, lack of environmental pollution, and ease of access, is considered an ideal alternative energy source. Piezoelectric nanogenerators (PENGs) can harvest energy from mechanical motion in the environment, converting mechanical energy into electrical energy, and have been widely researched and applied in piezoelectronics, self-powered sensors, and energy harvesters. Compared to the commonly studied brittle piezoelectric materials such as BaTiO3 (BTO) and lead zirconate titanate (PZT), piezoelectric polymer materials (such as polyvinylidene fluoride (PVDF)) have advantages such as high flexibility, good compatibility, light weight, and ease of processing. They also have good potential applications in flexible wearable devices, making piezoelectric polymer materials a new choice for the preparation of PENGs.

[0003] PVDF is a semi-crystalline polymer, mainly consisting of five crystalline phases: α, β, γ, δ, and ε. Among them, the β phase exhibits excellent piezoelectric properties due to its all-trans (TTTT) conformation and the largest electric dipole moment. Therefore, the key to preparing PENGs using piezoelectric polymer materials such as PVDF is to increase the β phase content in the PVDF chain. Filler doping, as a method to increase the β phase content, has received widespread attention and research due to its simplicity and significant effects.

[0004] Perovskite materials are used as a dopant filler in PVDF fabrication for PENGs due to their intrinsic piezoelectric properties and spontaneous polarization effect. The piezoelectric output voltage and current of the CsPbBr3@PVDF-based PENG are 33 V and 300 nA·cm, respectively. -2 The piezoelectric output performance is approximately four times higher than that of PENG based on pure PVDF. The doping of CsPbBr3 nanoparticles significantly improves the piezoelectric properties of the composite material, primarily due to the presence of a built-in electric field within the composite. This built-in electric field effectively induces the migration and aggregation of free electrons at the interface between PVDF and the doped nanoparticles, leading to spontaneous polarization of the PVDF dipoles and thus increasing the β-phase content of the PVDF. Therefore, successfully generating a strong built-in electric field within the PVDF bulk to induce spontaneous polarization of the PVDF is crucial for improving the piezoelectric properties of perovskite@PVDF composites.

[0005] The strength of the built-in electric field is related to the polarity of the material; polarity is beneficial for generating a robust built-in electric field. Furthermore, studies have shown that metal ion doping can effectively improve the polarity and carrier mobility of semiconductor materials. Compared to commonly used APbX3 lead halide perovskites, lead-free double perovskites (A2B...)...I B III X6 not only has the advantages of being environmentally friendly and having good stability, but more importantly, it can enhance A2B to a greater extent through B-site doping / alloying. I B III The polarity of X6, resulting in a stronger built-in electric field that induces PVDF crystallization into the β phase, shows promise as a better option. However, there is currently no research on using metal doping to improve the performance of PENG based on double perovskite@PVDF thin films. Summary of the Invention

[0006] The purpose of this invention is to address the aforementioned problems in the prior art by proposing a piezoelectric composite material to improve the β-phase content and piezoelectric properties of PVDF.

[0007] The objective of this invention can be achieved through the following technical solutions:

[0008] A piezoelectric composite material, said composite material being composed of Zr / Te co-doped Cs₂Ag 0.3 Na 0.7 It was prepared by combining InCl6 double perovskite and PVDF.

[0009] In the aforementioned piezoelectric composite material, Zr / Te co-doped Cs2Ag 0.3 Na 0.7 The mass ratio of InCl6 double perovskite to PVDF is 1:(10-15).

[0010] Preferably, PVDF has a molecular weight of 780,000.

[0011] In the aforementioned piezoelectric composite material, Zr / Te co-doped Cs2Ag 0.3 Na 0.7 The preparation method of InCl6 double perovskite includes the following steps: mixing ZrCl4, TeO2, CsCl, AgCl, NaCl, InCl3 and HCl, then reacting at high temperature, and finally drying to obtain Zr / Te co-doped Cs2Ag. 0.3 Na 0.7 InCl6 double perovskite.

[0012] In the aforementioned piezoelectric composite material, the high-temperature reaction temperature is 160-190℃, and the time is 8-12h.

[0013] In the aforementioned piezoelectric composite material, the molar ratio of ZrCl4, TeO2, and CsCl is (10-15):1:(75-85).

[0014] In the aforementioned piezoelectric composite material, the molar ratio of CsCl, AgCl, NaCl, and InCl3 is (5-8):1:(2-3):(3-4).

[0015] This invention provides a method for preparing a piezoelectric composite material, the method comprising the following steps:

[0016] S1, Cs2Ag co-doped with Zr / Te 0.3 Na 0.7 InCl6 double perovskite was added to a mixture of N,N-dimethylformamide containing PVDF and stirred evenly.

[0017] S2. Then, the coating is transferred to a glass plate, vacuum dried, and after cooling, it is peeled off from the glass plate to obtain the piezoelectric composite material.

[0018] In the above-mentioned method for preparing a piezoelectric composite material, the PVDF concentration in the N,N-dimethylformamide mixture containing PVDF is 0.1-0.2 g / ml.

[0019] In the above-mentioned method for preparing a piezoelectric composite material, the vacuum drying temperature is 75-85℃ and the time is 1-3h.

[0020] In this invention, the pore size and distribution of the prepared double perovskite are strictly affected by heating temperature and time. Simultaneously, the distribution of the double perovskite within the PVDF in the piezoelectric composite material is influenced by stirring time and temperature. Furthermore, the piezoelectric properties of the piezoelectric composite material and the resulting PENG are strictly affected by the content of the added double perovskite.

[0021] The present invention also provides a piezoelectric nanogenerator, the generator comprising the above-described piezoelectric composite material or the piezoelectric composite material prepared by the above method.

[0022] Preferably, the piezoelectric voltage of the piezoelectric nanogenerator is 65-70V.

[0023] The present invention also provides a method for preparing the above-mentioned piezoelectric nanogenerator. First, an aluminum foil layer is covered on one side of the piezoelectric composite material as a lower electrode layer, and the lower electrode layer is fixed on a polyethylene terephthalate (PET) sheet that provides support. Then, a layer of polydimethylsiloxane (PDMS) is coated on the other side of the composite material and covered with aluminum foil as an upper electrode layer before the PDMS is cured. Leads are led out from both ends of the upper electrode layer and the lower electrode layer and fixed with silver paste for electrical signal testing. The above device is encapsulated with polyimide (PI) tape to obtain a piezoelectric nanogenerator (PENG).

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The piezoelectric composite material obtained by this invention is based on Zr / Te co-doped Cs2Ag. 0.3 Na 0.7 The InCl6 double perovskite@PVDF composite film test results show that, compared with Cs2Ag 0.3 Na 0.7 InCl6 double perovskite filler, with Zr / Te co-doped Cs2Ag incorporated into a PVDF matrix. 0.3 Na 0.7 InCl6 double perovskite filler can significantly increase the β phase content, and the Cs2Ag content can be significantly increased by appropriately adding Zr and Te doping amounts. 0.3 Na 0.7 The polarity of InCl6 crystals creates a strong embedded electric field, which enhances the dielectric properties and spontaneous polarization effect of the composite film.

[0026] 2. The Zr / Te co-doped Cs2Ag piezoelectric composite material of the present invention 0.3 Na 0.7 InCl6 double perovskite@PVDF-based PENGs exhibit excellent piezoelectric output performance, with a maximum open-circuit voltage and short-circuit current density of 67 V and 18 μA·cm⁻¹, respectively. -2 These figures are 20 times and 13 times that of pure PVDF-based PENG, respectively, and are higher than those of undoped Cs2Ag. 0.3 Na 0.7 InCl6 double perovskite@PVDF-based PENG is 3 and 5 times more potent than single-doped Zr Cs2Ag. 0.3 Na 0.7 2x and 3x InCl6 double perovskite@PVDF-based PENG. Attached Figure Description

[0027] Figure 1 The Zr / Te co-doped Cs2Ag prepared in Example 1 of this invention 0.3 Na 0.7 Scanning electron microscope (SEM) image of InCl6@PVDF composite film.

[0028] Figure 2 The Zr / Te co-doped Cs2Ag prepared in Example 1 of this invention 0.3 Na 0.7 The dielectric constant of the InCl6@PVDF composite film varies at different frequencies.

[0029] Figure 3 The Zr / Te co-doped Cs2Ag prepared in Example 1 of this invention 0.3 Na 0.7 Polarization electric field (PE) curves of InCl6@PVDF composite film.

[0030] Figure 4 The Zr / Te co-doped Cs2Ag prepared in Example 1 of this invention 0.3 Na 0.7 The piezoelectric voltage of InCl6@PVDF composite film based on PENG.

[0031] Figure 5 This is a scanning electron microscope (SEM) image of the pure PVDF thin film prepared in Example 2 of the present invention.

[0032] Figure 6 The piezoelectric voltage of the pure PVDF thin film-based PENG obtained in Example 2 of this invention is given.

[0033] Figure 7 The Cs2Ag obtained in Example 3 of this invention 0.3 Na 0.7 The piezoelectric voltage of InCl6@PVDF composite film based on PENG.

[0034] Figure 8 The Zr-doped Cs2Ag prepared in Example 4 of this invention 0.3 Na 0.7 The piezoelectric voltage of InCl6@PVDF composite film based on PENG.

[0035] Figure 9 The images show a comparison of X-ray powder diffraction (XRD) of different composite films prepared in Examples 1 and 2-4 of this invention.

[0036] Figure 10 This is a comparison of the Fourier transform infrared (FTIR) spectra of different composite films prepared in Examples 1 and 2-4 of the present invention.

[0037] Figure 11 The β phase content (F) of the different composite membranes prepared in Examples 1 and 2-4 of this invention is... β (%) Comparison chart.

[0038] Figure 12 This is a comparison diagram of the piezoelectric voltages of different composite film-based PENGs prepared in Examples 1 and 2-4 of the present invention.

[0039] Figure 13 When the amount of perovskite added in Example 5 of this invention is 3 wt.%, the Zr / Te co-doped Cs2Ag 0.3 Na 0.7 Scanning electron microscope (SEM) image of InCl6@PVDF composite film.

[0040] Figure 14 When the amount of perovskite added in Example 5 of this invention is 3 wt.%, the Zr / Te co-doped Cs2Ag0.3 Na 0.7 The piezoelectric voltage of InCl6@PVDF composite film based on PENG.

[0041] Figure 15 When the amount of perovskite added in Example 6 of this invention is 6 wt.%, the Zr / Te co-doped Cs2Ag 0.3 Na 0.7 Scanning electron microscope (SEM) image of InCl6@PVDF composite film.

[0042] Figure 16 When the amount of perovskite added in Example 6 of this invention is 6 wt.%, the Zr / Te co-doped Cs2Ag 0.3 Na 0.7 The piezoelectric voltage of InCl6@PVDF composite film based on PENG.

[0043] Figure 17 When the amount of perovskite added in Example 7 of this invention is 12 wt.%, the Zr / Te co-doped Cs2Ag 0.3 Na 0.7 Scanning electron microscope (SEM) image of InCl6@PVDF composite film.

[0044] Figure 18 When the amount of perovskite added in Example 7 of this invention is 12 wt.%, the Zr / Te co-doped Cs2Ag 0.3 Na 0.7 The piezoelectric voltage of InCl6@PVDF composite film based on PENG.

[0045] Figure 19 This is a comparison diagram of the piezoelectric voltages of different composite film-based PENGs prepared in Examples 1, 2, and 5-7 of the present invention. Detailed Implementation

[0046] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0047] Example 1:

[0048] S1. Mix 0.6 mmol ZrCl4, 0.05 mmol TeO2, 4 mmol CsCl, 0.6 mmol AgCl, 1.4 mmol NaCl, 2 mmol InCl3, and 20 mL HCl in a polytetrafluoroethylene liner until homogeneous. Then transfer the mixture to a 50 mL Teflon stainless steel autoclave and maintain the mixture in a muffle oven at 180 °C for 10 h to prepare Zr / Te co-doped Cs2Ag. 0.3 Na 0.7InCl6 double perovskite was washed with deionized water, centrifuged, and dried in air at 60°C for 3 hours.

[0049] S2. Add 1.5g PVDF and 10mL N,N-dimethylformamide (DMF) to a beaker and stir with a magnetic stirrer at 60℃ for 2h until a homogeneous solution is obtained.

[0050] S3. Add 135 mg (9 wt.%) of dried double perovskite to the DMF mixed solution containing PVDF and stir at 50 °C for 2 h until the two are uniformly mixed;

[0051] S4. Transfer the mixed solution onto a glass slide using a pipette and coat it with a coating machine. Then, place the glass slide in a vacuum drying oven and anneal and dry it at 80°C for 2 hours. After naturally cooling to room temperature, peel it off from the glass slide to obtain Cs₂Ag co-doped with Zr / Te at an addition amount of 9 wt.%. 0.3 Na 0.7 InCl6@PVDF composite membrane;

[0052] S6, First, in Zr / Te co-doped Cs2Ag 0.3 Na 0.7 An aluminum foil layer is covered on one side of the InCl6@PVDF composite film as the lower electrode layer, and the lower electrode layer is fixed on a polyethylene terephthalate (PET) sheet that provides support. Then, a layer of polydimethylsiloxane (PDMS) is coated on the other side of the composite film, and aluminum foil is covered on the other side before the PDMS is cured to serve as the upper electrode layer. Leads are led out from both ends of the upper and lower electrode layers and fixed with silver paste for electrical signal testing. The above device is encapsulated with polyimide (PI) tape to obtain a piezoelectric nanogenerator (PENG).

[0053] The Cs₂Ag co-doped with Zr / Te and containing 9 wt.% of double perovskite was prepared in Example 1. 0.3 Na 0.7 The microstructure of the InCl6@PVDF composite film is as follows: Figure 1 As shown in the SEM, observation reveals Zr / Te co-doped Cs2Ag. 0.3 Na 0.7 InCl6 was uniformly distributed on the PVDF film without significant aggregation, and the added Zr / Te co-doped Cs2Ag 0.3 Na 0.7 The InCl6 particles are uniform in size, approximately 100 nm. The uniform dispersion of the double perovskite within the PVDF effectively ensures the high piezoelectric properties of the composite film.

[0054] The polarity of a molecule is positively correlated with its dielectric constant; the higher the dielectric constant, the greater its polarity. The dielectric constant variation of a Zr / Te co-doped Cs₂Ag₀.₃Na₀.₇InCl₆@PVDF composite film with 9 wt.% Zr / Te doping is shown in the figure below. Figure 2 As shown, the dielectric constant of the composite film reaches 20.08 at a frequency of 100kHz. Such a high dielectric constant indicates high polarity in the composite film; greater polarity is more conducive to the spontaneous polarization effect of the composite film. The polarization-electric field (PE) curve of the composite film is shown below. Figure 3 As shown, the excellent PE curve shape indicates that the composite film possesses good ferroelectricity and a high spontaneous polarization effect. This high spontaneous polarization effect causes the α-phase of PVDF to transform into the β-phase. The addition of perovskite increases the β-phase content of the composite film, ensuring its high piezoelectric performance. The piezoelectric voltage of the composite film is shown below. Figure 4 As shown, it can be confirmed that the Zr / Te co-doped Cs2Ag with a double perovskite addition of 9 wt.% is effective. 0.3 Na 0.7 The maximum open-circuit voltage of the InCl6@PVDF composite membrane can reach 67V.

[0055] Example 2:

[0056] S1. Add 1.5g PVDF and 10mL N,N-dimethylformamide (DMF) to a beaker and stir with a magnetic stirrer at 60℃ for 2h until a homogeneous solution is obtained.

[0057] S2. Transfer the above solution onto a glass slide using a pipette and coat it using a coating machine. Then, place the glass slide in a vacuum drying oven and anneal and dry it at 80°C for 2 hours. After naturally cooling to room temperature, the pure PVDF film can be peeled off from the glass slide.

[0058] S3. First, an aluminum foil layer is covered on one side of the pure PVDF film as the lower electrode layer, and the lower electrode layer is fixed on the polyethylene terephthalate (PET) sheet that provides support. Then, a layer of polydimethylsiloxane (PDMS) is coated on the other side of the composite film, and aluminum foil is covered on the other side before the PDMS is cured as the upper electrode layer. Leads are drawn from both ends of the upper electrode layer and the lower electrode layer and fixed with silver paste for electrical signal testing. The above device is encapsulated with polyimide (PI) tape to obtain a piezoelectric nanogenerator (PENG).

[0059] The microstructure of the pure PVDF film prepared in Example 2 is as follows: Figure 5 As shown in the SEM, the pure PVDF film exhibits a blanket-like structure with a large comparative area. However, the staggered arrangement of each PVDF molecular chain may hinder electron conduction throughout the film, resulting in low piezoelectric properties of the pure PVDF film.

[0060] The piezoelectric voltage of pure PVDF film is as follows Figure 6 As shown, the maximum open-circuit voltage of the pure PVDF film is 3.9V, which is approximately the same as that of Cs₂Ag co-doped with Zr / Te and containing 9wt.% perovskite. 0.3 Na 0.7 One-twentieth of the InCl6@PVDF composite membrane. This result fully demonstrates the effectiveness of Zr / Te co-doped Cs2Ag. 0.3 Na 0.7 InCl6 has a good effect on improving the piezoelectric properties of PVDF.

[0061] Example 3:

[0062] S1. Mix 4 mmol CsCl, 0.6 mmol AgCl, 1.4 mmol NaCl, 2 mmol InCl3, and 20 mL HCl in a polytetrafluoroethylene liner until homogeneous. Then transfer the mixture to a 50 mL Teflon stainless steel autoclave and maintain the mixture in a muffle oven at 180 °C for 10 h to prepare Cs2Ag. 0.3 Na 0.7 InCl6 double perovskite was washed with deionized water, centrifuged, and dried in air at 60°C for 3 hours.

[0063] S2. Add 1.5g PVDF and 10mL N,N-dimethylformamide (DMF) to a beaker and stir with a magnetic stirrer at 60℃ for 2h until a homogeneous solution is obtained.

[0064] S3. Add 135 mg (9 wt.%) of dried double perovskite to the DMF mixed solution containing PVDF and stir at 50 °C for 2 h until the two are uniformly mixed;

[0065] S4. Transfer the mixed solution onto a glass slide using a pipette and coat it with a coating machine. Then, place the glass slide in a vacuum drying oven and anneal and dry it at 80°C for 2 hours. After naturally cooling to room temperature, the 9 wt.% Cs2Ag can be peeled off from the glass slide. 0.3 Na 0.7 InCl6@PVDF composite membrane;

[0066] S5, First in Cs2Ag 0.3 Na 0.7An aluminum foil layer is covered on one side of the InCl6@PVDF composite film as the lower electrode layer, and the lower electrode layer is fixed on a polyethylene terephthalate (PET) sheet that provides support. Then, a layer of polydimethylsiloxane (PDMS) is coated on the other side of the composite film, and aluminum foil is covered on the other side before the PDMS is cured to serve as the upper electrode layer. Leads are led out from both ends of the upper and lower electrode layers and fixed with silver paste for electrical signal testing. The above device is encapsulated with polyimide (PI) tape to obtain a piezoelectric nanogenerator (PENG).

[0067] The Cs₂Ag double perovskite prepared in Example 3 had an addition amount of 9 wt.% 0.3 Na 0.7 The piezoelectric voltage of the InCl6@PVDF composite film is as follows: Figure 7 As shown, the maximum open-circuit voltage of this composite membrane reaches approximately 20V, which is only about the same as that of Cs₂Ag co-doped with Zr / Te and containing 9wt.% perovskite. 0.3 Na 0.7 One-third of the InCl6@PVDF composite membrane. This may be due to the presence of Cs2Ag. 0.3 Na 0.7 The doping of Zr / Te into InCl6 double perovskites shifts the positive and negative charges of the perovskite molecules, thereby increasing their molecular polarity. The more polar Zr / Te co-doped Cs₂Ag... 0.3 Na 0.7 InCl6 generates a larger built-in electric field in the PVDF matrix, which induces spontaneous polarization in PVDF to a greater extent and increases its β content, thereby enhancing its piezoelectric properties.

[0068] Example 4:

[0069] S1. Mix 0.6 mmol ZrCl4, 4 mmol CsCl, 0.6 mmol AgCl, 1.4 mmol NaCl, 2 mmol InCl3, and 20 mL HCl in a polytetrafluoroethylene liner until homogeneous. Then transfer the mixture to a 50 mL Teflon stainless steel autoclave and maintain the mixture in a muffle oven at 180 °C for 10 h to prepare Zr-doped Cs2Ag. 0.3 Na 0.7 InCl6 double perovskite was washed with deionized water, centrifuged, and dried in air at 60°C for 3 hours.

[0070] S2. Add 1.5g PVDF and 10mL N,N-dimethylformamide (DMF) to a beaker and stir with a magnetic stirrer at 60℃ for 2h until a homogeneous solution is obtained.

[0071] S3. Add 135 mg (9 wt.%) of dried double perovskite to the DMF mixture containing PVDF and stir at 50 °C for 2 h until the two are uniformly mixed;

[0072] S4. Transfer the mixed solution onto a glass slide using a pipette and coat it with a coating machine. Then, place the glass slide in a vacuum drying oven and anneal and dry it at 80°C for 2 hours. After naturally cooling to room temperature, the Zr-doped Cs₂Ag with an addition of 9 wt.% can be peeled off from the glass slide to obtain Cs₂Ag with a Zr addition of 9 wt.%. 0.3 Na 0.7 InCl6@PVDF composite membrane;

[0073] S5, First, in Zr-doped Cs2Ag 0.3 Na 0.7 An aluminum foil layer is covered on one side of the InCl6@PVDF composite film as the lower electrode layer, and the lower electrode layer is fixed on a polyethylene terephthalate (PET) sheet that provides support. Then, a layer of polydimethylsiloxane (PDMS) is coated on the other side of the composite film, and aluminum foil is covered on the other side before the PDMS is cured to serve as the upper electrode layer. Leads are led out from both ends of the upper and lower electrode layers and fixed with silver paste for electrical signal testing. The above device is encapsulated with polyimide (PI) tape to obtain a piezoelectric nanogenerator (PENG).

[0074] The Zr-doped Cs₂Ag with a double perovskite addition of 9 wt.% was prepared in Example 4. 0.3 Na 0.7 The piezoelectric voltage of the InCl6@PVDF composite film is as follows: Figure 8 As shown, the maximum open-circuit voltage of this composite membrane reaches approximately 40V, while the Cs₂Ag co-doped Zr / Te with a double perovskite content of 9wt.% exhibits this characteristic. 0.3 Na 0.7 The 67V of the InCl6@PVDF composite film is approximately 1.5 times that of the others. This is likely due to the presence of Zr-doped Cs2Ag. 0.3 Na 0.7 Further doping of Te into InCl6 double perovskites results in a greater shift in the positive and negative charges of the perovskite molecules, thus increasing their molecular polarity more significantly. This leads to the more polar Zr / Te co-doped Cs₂Ag... 0.3 Na 0.7 InCl6 generates a larger built-in electric field in the PVDF matrix, inducing spontaneous polarization in PVDF to a greater extent, increasing the β content of the composite film, and ultimately leading to better Zr / Te co-doped Cs2Ag. 0.3 Na 0.7 The InCl6@PVDF composite film exhibits such high piezoelectric properties.

[0075] The change in β content of the composite film before and after the addition of perovskite can be seen from... Figure 9 XRD patterns and Figure 10 The FTIR spectra were verified. XRD clearly showed that the diffraction peaks of the α phase belonging to PVDF disappeared after the addition of the double perovskite, leaving only the diffraction peaks of the β phase. This result was also reflected in the FTIR. Furthermore, the β content (Fo) of the composite film before and after the addition of different double perovskites was calculated using a formula. β (%), the results are as follows Figure 11 As shown in the figure. It can be seen that after adding the double perovskite, the F of PVDF... β (%) increased significantly, especially with the addition of Zr / Te co-doped Cs2Ag 0.3 Na 0.7 After InCl6 double perovskite, the F of the composite film β The piezoelectric properties of PVDF (%) are more than twice that of pure PVDF, confirming the validity of the claim that double perovskite fillers can significantly enhance the piezoelectric properties of PVDF. A comparison of the piezoelectric voltage performance of Examples 1-4 is provided. Figure 12 As shown, Cs2Ag doped with different metal ions can be clearly observed. 0.3 Na 0.7 The improvement effect of InCl6 double perovskite on the piezoelectric properties of PVDF, and the Zr / Te co-doped Cs2Ag 0.3 Na 0.7 InCl6 double perovskite has the most significant effect on improving the piezoelectric properties of PVDF.

[0076] Example 5:

[0077] S1. Mix 0.6 mmol ZrCl4, 0.05 mmol TeO2, 4 mmol CsCl, 0.6 mmol AgCl, 1.4 mmol NaCl, 2 mmol InCl3, and 20 mL HCl in a polytetrafluoroethylene liner until homogeneous. Then transfer the mixture to a 50 mL Teflon stainless steel autoclave and maintain it in a muffle oven at 180 °C for 10 h to prepare Zr / Te co-doped Cs2Ag. 0.3 Na 0.7 InCl6 double perovskite was washed with deionized water, centrifuged, and dried in air at 60°C for 3 hours.

[0078] S2. Add 1.5g PVDF and 10mL N,N-dimethylformamide (DMF) to a beaker and stir with a magnetic stirrer at 60℃ for 2h until a homogeneous solution is obtained.

[0079] S3. Add 45 mg (3 wt.%) of dried double perovskite to the DMF mixture containing PVDF and stir at 50 °C for 2 h until the two are uniformly mixed;

[0080] S4. Transfer the mixed solution onto a glass slide using a pipette and coat it with a coating machine. Then, place the glass slide in a vacuum drying oven and anneal and dry it at 80°C for 2 hours. After naturally cooling to room temperature, the Zr / Te co-doped Cs₂Ag with an addition amount of 3 wt.% can be peeled off from the glass slide to obtain Cs₂Ag with an addition amount of 3 wt.%. 0.3 Na 0.7 InCl6@PVDF composite membrane;

[0081] S5, First, in Zr / Te co-doped Cs2Ag 0.3 Na 0.7 An aluminum foil layer is covered on one side of the InCl6@PVDF composite film as the lower electrode layer, and the lower electrode layer is fixed on a polyethylene terephthalate (PET) sheet that provides support. Then, a layer of polydimethylsiloxane (PDMS) is coated on the other side of the composite film, and aluminum foil is covered on the other side before the PDMS is cured to serve as the upper electrode layer. Leads are led out from both ends of the upper and lower electrode layers and fixed with silver paste for electrical signal testing. The above device is encapsulated with polyimide (PI) tape to obtain a piezoelectric nanogenerator (PENG).

[0082] The Cs₂Ag co-doped with Zr / Te and containing 3 wt.% perovskite was prepared in Example 5. 0.3 Na 0.7 The microstructure of the InCl6@PVDF composite film is as follows: Figure 13 As shown in the SEM images, only a small amount of Zr / Te co-doped Cs2Ag can be observed. 0.3 Na 0.7 InCl6 is distributed on the PVDF film. The piezoelectric voltage of the composite film is as follows: Figure 14 As shown, Cs₂Ag co-doped with Zr / Te and containing 3 wt.% of double perovskite can be observed. 0.3 Na 0.7 The maximum open-circuit voltage of the InCl6@PVDF composite membrane is only about 15V. This may be due to the insufficient amount of added double perovskite, resulting in a small increase in the β-phase content of PVDF.

[0083] Example 6:

[0084] S1. Mix 0.6 mmol ZrCl4, 0.05 mmol TeO2, 4 mmol CsCl, 0.6 mmol AgCl, 1.4 mmol NaCl, 2 mmol InCl3, and 20 mL HCl in a polytetrafluoroethylene liner until homogeneous. Then transfer the mixture to a 50 mL Teflon stainless steel autoclave and maintain it in a muffle oven at 180 °C for 10 h to prepare Zr / Te co-doped Cs2Ag. 0.3 Na 0.7InCl6 double perovskite was washed with deionized water, centrifuged, and dried in air at 60°C for 3 hours.

[0085] S2. Add 1.5g PVDF and 10mL N,N-dimethylformamide (DMF) to a beaker and stir with a magnetic stirrer at 60℃ for 2h until a homogeneous solution is obtained.

[0086] S3. Add 90 mg (6 wt.%) of dried double perovskite to the DMF mixture containing PVDF and stir at 50 °C for 2 h until the two are uniformly mixed;

[0087] S4. Transfer the mixed solution onto a glass slide using a pipette and coat it with a coating machine. Then, place the glass slide in a vacuum drying oven and anneal and dry it at 80°C for 2 hours. After naturally cooling to room temperature, the Zr / Te co-doped Cs₂Ag with an addition amount of 6 wt.% can be peeled off from the glass slide to obtain Cs₂Ag with an addition amount of 6 wt.%. 0.3 Na 0.7 InCl6@PVDF composite membrane;

[0088] S5, First, in Zr / Te co-doped Cs2Ag 0.3 Na 0.7 An aluminum foil layer is covered on one side of the InCl6@PVDF composite film as the lower electrode layer, and the lower electrode layer is fixed on a polyethylene terephthalate (PET) sheet that provides support. Then, a layer of polydimethylsiloxane (PDMS) is coated on the other side of the composite film, and aluminum foil is covered on the other side before the PDMS is cured to serve as the upper electrode layer. Leads are led out from both ends of the upper and lower electrode layers and fixed with silver paste for electrical signal testing. The above device is encapsulated with polyimide (PI) tape to obtain a piezoelectric nanogenerator (PENG).

[0089] The Cs₂Ag co-doped with Zr / Te and containing 6 wt.% of double perovskite was prepared in Example 6. 0.3 Na 0.7 The microstructure of the InCl6@PVDF composite film is as follows: Figure 15 As shown in the SEM, Zr / Te co-doped Cs2Ag can be observed distributed on the PVDF matrix. 0.3 Na 0.7 The amount of InCl6 distributed is significantly increased. The piezoelectric voltage of the composite film is as follows: Figure 16 As shown, Cs₂Ag co-doped with Zr / Te and containing 6 wt.% of double perovskite can be observed. 0.3 Na 0.7 The maximum open-circuit voltage of the InCl6@PVDF composite film increased to approximately 25V. This result indicates that the greater the amount of added double perovskite, the greater the improvement in the β-phase content and piezoelectric properties of PVDF.

[0090] Example 7:

[0091] S1. Mix 0.6 mmol ZrCl4, 0.05 mmol TeO2, 4 mmol CsCl, 0.6 mmol AgCl, 1.4 mmol NaCl, 2 mmol InCl3, and 20 mL HCl in a polytetrafluoroethylene liner until homogeneous. Then transfer the mixture to a 50 mL Teflon stainless steel autoclave and maintain it in a muffle oven at 180 °C for 10 h to prepare Zr / Te co-doped Cs2Ag. 0.3 Na 0.7 InCl6 double perovskite was washed with deionized water, centrifuged, and dried in air at 60°C for 3 hours.

[0092] S2. Add 1.5g PVDF and 10mL N,N-dimethylformamide (DMF) to a beaker and stir with a magnetic stirrer at 60℃ for 2h until a homogeneous solution is obtained.

[0093] S3. Add 180 mg (12 wt.%) of dried double perovskite to the DMF mixture containing PVDF and stir at 50 °C for 2 h until the two are evenly mixed;

[0094] S4. Transfer the mixed solution onto a glass slide using a pipette and coat it with a coating machine. Then, place the glass slide in a vacuum drying oven and anneal and dry it at 80°C for 2 hours. After naturally cooling to room temperature, the Zr / Te co-doped Cs₂Ag with an addition amount of 12 wt.% can be peeled off from the glass slide to obtain Cs₂Ag with an addition amount of 12 wt.%. 0.3 Na 0.7 InCl6@PVDF composite membrane;

[0095] S5, First, in Zr / Te co-doped Cs2Ag 0.3 Na 0.7 An aluminum foil layer is covered on one side of the InCl6@PVDF composite film as the lower electrode layer, and the lower electrode layer is fixed on a polyethylene terephthalate (PET) sheet that provides support. Then, a layer of polydimethylsiloxane (PDMS) is coated on the other side of the composite film, and aluminum foil is covered on the other side before the PDMS is cured to serve as the upper electrode layer. Leads are led out from both ends of the upper and lower electrode layers and fixed with silver paste for electrical signal testing. The above device is encapsulated with polyimide (PI) tape to obtain a piezoelectric nanogenerator (PENG).

[0096] The Zr / Te co-doped Cs₂Ag prepared in Example 7 had a double perovskite content of 12 wt.% 0.3 Na 0.7 The microstructure of the InCl6@PVDF composite film is as follows: Figure 17As shown in the SEM, Zr / Te co-doped Cs2Ag can be observed distributed on the PVDF matrix. 0.3 Na 0.7 InCl6 double perovskite aggregates begin to aggregate. The piezoelectric voltage of the composite film is as follows: Figure 18 As shown, Cs₂Ag co-doped with Zr / Te and containing 12 wt.% of double perovskite can be observed. 0.3 Na 0.7 The maximum open-circuit voltage of the InCl6@PVDF composite film reaches approximately 38V, which is significantly lower than that of the Cs2Ag co-doped Zr / Te film with a double perovskite content of 9wt.%. 0.3 Na 0.7 The InCl6@PVDF composite film showed a piezoelectric value of 67V. This result indicates that when the amount of added perovskite is too large, the perovskite begins to agglomerate within the PVDF. The formation of perovskite agglomerates not only causes adjacent dipoles to cancel each other out, hindering the phase transition of the PVDF, but also restricts the uniform deformation of the composite film, thereby reducing the open-circuit piezoelectric value.

[0097] Comparison of piezoelectric voltage performance of Examples 1-2 and Examples 5-7 Figure 19 As shown, it is evident that different amounts of Zr / Te co-doped Cs2Ag can be clearly observed. 0.3 Na 0.7 The improvement effect of InCl6 double perovskite on the piezoelectric properties of PVDF, and the effect of Zr / Te co-doped Cs2Ag 0.3 Na 0.7 The piezoelectric properties of the composite film are optimal when the addition amount of InCl6 double perovskite is 9 wt.%.

[0098] In summary, this invention utilizes different metal doping methods and varying amounts of Cs₂Ag. 0.3 Na 0.7 Using InCl6 double perovskite as a filler to modify PVDF can indeed achieve a phase transition in PVDF, significantly increasing the β-phase content of PVDF and effectively improving the piezoelectric properties of the composite film. This is due to the doping of Cs2Ag with metal ions such as Zr and Te. 0.3 Na 0.7 InCl6 double perovskite increases the polarity of the double perovskite. When the more polar double perovskite is incorporated into PVDF, the more obvious polarity difference leads to a stronger charge accumulation effect. Under the intermolecular forces, more electrons or ions in the composite film accumulate at the interface between the two regions, resulting in a stronger built-in electric field in the PVDF matrix and more induced spontaneous polarization effect. This greatly enhances the α-phase to β-phase transition of PVDF and ultimately endows the composite film with high piezoelectric properties.

[0099] The embodiments described herein cover any points not exhaustively within the scope of the technical claims of this invention, as well as new technical solutions formed by equivalent substitutions of one or more technical features in the embodiments. These are all within the scope of the claims of this invention. Furthermore, in all listed or unlisted embodiments of this invention, each parameter in the same embodiment merely represents an instance (i.e., a feasible solution) of its technical solution, and there is no strict coordination or limitation relationship between the parameters. The parameters can be substituted for each other without violating axioms and the claims of this invention, unless otherwise stated.

[0100] The technical means disclosed in this invention are not limited to those described above, but also include technical solutions composed of any combination of the above technical features. The above descriptions are specific embodiments of this invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of this invention, and these improvements and modifications are also considered within the scope of protection of this invention.

[0101] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.

Claims

1. A piezoelectric composite material, characterized in that, The composite material is composed of Zr / Te co-doped Cs2Ag. 0.3 Na 0.7 It was prepared from InCl6 double perovskite and PVDF; Zr / Te co-doped Cs2Ag 0.3 Na 0.7 The mass ratio of InCl6 double perovskite to PVDF is 1:(10-15).

2. The piezoelectric composite material according to claim 1, characterized in that, Zr / Te co-doped Cs2Ag 0.3 Na 0.7 The preparation method of InCl6 double perovskite includes the following steps: mixing ZrCl4, TeO2, CsCl, AgCl, NaCl, InCl3 and HCl, then reacting at high temperature, and finally drying to obtain Zr / Te co-doped Cs2Ag. 0.3 Na 0.7 InCl6 double perovskite.

3. The piezoelectric composite material according to claim 2, characterized in that, The high-temperature reaction temperature is 160-190℃, and the time is 8-12h.

4. The piezoelectric composite material according to claim 2, characterized in that, The molar ratio of ZrCl4, TeO2 and CsCl is (10-15):1:(75-85).

5. The piezoelectric composite material according to claim 2, characterized in that, The molar ratio of CsCl, AgCl, NaCl and InCl3 is (5-8):1:(2-3):(3-4).

6. A method for preparing the piezoelectric composite material as described in claim 1, characterized in that, The method includes the following steps: S1, Cs2Ag co-doped with Zr / Te 0.3 Na 0.7 InCl6 double perovskite was added to a mixture of N,N-dimethylformamide containing PVDF and stirred evenly. S2. Then, the coating is transferred to a glass plate, vacuum dried, and after cooling, it is peeled off from the glass plate to obtain the piezoelectric composite material.

7. The method for preparing a piezoelectric composite material according to claim 6, characterized in that, The concentration of PVDF in the N,N-dimethylformamide mixture containing PVDF is 0.1-0.2 g / ml.

8. The method for preparing a piezoelectric composite material according to claim 6, characterized in that, Vacuum drying temperature is 75-85℃, time is 1-3h.

9. A piezoelectric nanogenerator, characterized in that, The generator comprises the piezoelectric composite material according to claims 1-5 or the piezoelectric composite material prepared by the method according to claims 7-8.

Citation Information

Patent Citations

  • Bismuth ferrite / polyvinylidene fluoride-trifluoroethylene multilayer composite film and preparation method thereof

    CN111662469A

  • Piezoelectric composite material, piezoelectric composite film, preparation method of piezoelectric composite film and piezoelectric device

    CN111697124A